Probiotics Enhance Bone Density and Reduce Inflammation Postalveolar Surgery - Dongjie Fu; Xiaoxiang He; Jian Lu; Ting Du (International Dental Journal, 2025)
Background: This study aimed to evaluate the clinical efficacy of probiotic-based interventions in modulating the inflammatory response of periapical tissues and maintaining alveolar bone homeostasis following oral alveolar surgery. Method: In this open-label, nonblinded trial, 80 patients undergoing alveolar surgery were randomised into an experimental group (n = 40) receiving postoperative Lactobacillus reuteri DSM 17938 probiotics (1010 CFU/d) and a control group (n = 40) receiving standard care. Alveolar bone density was measured via cone-beam computed tomography (CBCT) at 1, 3, and 5 months postsurgery. Oral microbial diversity (16S rRNA sequencing) and inflammatory markers (IL-1β, TNF-α, IL-6) were analysed at 3 months. Result: The experimental group demonstrated a 3.8% higher bone density than controls at all follow-ups (P < .05), alongside a 15.2% increase in microbial diversity (Shannon index, P < .05). Proinflammatory cytokines were significantly reduced (IL-1β: −18.5%; TNF-α: −22.1%; IL-6: −14.7%, P < .05). While the bone density improvement was modest, its statistical significance suggests potential clinical relevance for osseointegration. Probiotic supplementation attenuated inflammation and enhanced alveolar bone stability postsurgery. However, the nonblinded design limits generalizability. Conclusion: Probiotic-based interventions with Lactobacillus reuteri effectively modulated the inflammatory response and enhanced alveolar bone homeostasis postalveolar surgery in this cohort. While promising, future double-blind trials with larger cohorts are needed to confirm these findings and explore broader translational applications in bone regeneration strategies.